NOTES FROM PRACTICE/UIT DIE PRAKTYK - Sewpaul, Vishanthie (Social Work/Maatskaplike Werk, 2010)
I am an adoptive mother, and being a mother is one of the central aspects of my identity … I am not sure if there is a difference in identity between biological mother and adoptive mother, for I have not been a biological mother. What I do know is that my daughter and I share a bond and a love that would stand the test of time of any parent-child relationship. I have an equal faith that she is as unconditionally loved by her father, Paul, who risked breaking conventional stereotypes about masculinity in the way he cared for her – from clinic visits, changing diapers, bathing, dressing and feeding and carrying her on his back, and swaying her to sleep especially when the ugly pains of colic brought on uncontrollable crying. He was the constant in her life whenever my work required travelling. Yet it was a love that would be marred by fear as she grew up. If he could, he would have denied the biological parents out of existence – not out of vindictiveness, but for the sheer pain of loving in fear … and if it were left entirely up to him, he would have chosen not to tell at all.